Stress Regimes in the Lithosphere. - Engelder, Terry (Princeton legacy library., 2014)
The purpose of this book is to acquaint the geoscientist with issues associated with the debate over orientation and magnitude of stress in the lithosphere. Terry Engelder provides a broad understanding of the topic, while touching some of the specific details involved in the interpretation of stress data generated by the most commonly used measurement techniques. An understanding of stress in the lithosphere starts with an introduction to nomenclature based on three reference states of stress. Since rock strength governs differential stress magnitudes, stress regimes are identified accordi.